Barriers and drivers towards the incorporation of crop residue in the soil. Analysis of Italian farmers’ opinion with the theory of planned behaviour - Bechini, Luca; Costamagna, Chiara; Zavattaro, Laura; Grignani, Carlo; Bijttebier, Jo; Ruysschaert, Greet (Italian Journal of Agronomy, 2015)
Despite the benefits arising from incorporating crop residue in the soil, some farmers decide to burn or sell it. The objective of the work described in this paper was to quantify the adoption of crop residue incorporation by Italian farmers, and to identify the barriers and drivers that they perceive towards this agricultural management practice. We applied a behavioural approach, based on the theory of planned behaviour. In agriculture, this theory can be used to study individual farmer beliefs to understand the intention to adopt agricultural management practices. Based on preliminary semi-structured interviews with 24 farmers, we have prepared and disseminated a structured questionnaire in dairy farms in the plain of northern Italy, in arable farms in the plain of northern, central, and southern Italy, and in arable farms in the hill of central and southern Italy. The questionnaire contained questions to reveal subjective beliefs of the farmers on the outcomes of incorporating crop residue, and on the referents and control factors that might influence adoption. We have received 315 filled questionnaires from 16 regions and 54 provinces. The survey has identified major drivers and barriers towards the incorporation of crop residue in the soil. The main drivers were the expected improvement of soil quality (higher soil organic matter, improved structure and fertility), the expected increase of grain protein concentration in the following wheat crop, the availability of adequate machinery, the prohibition of burning crop residue, and the knowledge that incorporation is important (which emphasizes the importance of an effective advisory service). The main barriers were the costs of incorporation, the need to increase the use of nitrogen fertiliser when straw is incorporated, and the problems to sow the following crop in the presence of residue. While on the basis of the preliminary interviews we expected that the possibility to sell the straw and the slow residue decomposition in the soil could be barriers against residue incorporation in the soil, questionnaire results did not confirm this expectation. The survey did not indicate that farmers are particularly worried about crop residue as potential sources of weeds, pests and diseases. Even if the methodology applied did not identify any of the referents as important barriers or drivers, there were important differences with respect to the perceived opinion of the social environment between adopters and non-adopters. This emphasizes the importance of an encouraging social environment for the propagation of good practices.